Suspending Disbelief: The Algorithmic Theater of Student Computer Tracking Software - sarin, parth; Hill-Bonnet, Laura (Surveillance & Society, 2025)
Monitoring technologies are increasingly used in schools to track students’ digital activity—including web browsing, app use, and more—and can even follow them beyond the physical schoolhouse gates. Informed by interviews with twenty-two US-based teachers, we propose a theory of “algorithmic theater” that captures the negotiated role these technologies play as instruments of schooling and state control. This theory situates the relationship among labor, performativity, infrastructure, and audience in the production of an algorithmic script, much as a theater company employs those elements in producing a play. We use algorithmic theater to frame the teachers’ statements about these technologies and to disentangle the coordinated and contested narratives about algorithmic omniscience, efficiency, and care from the material realities of the classroom. For example, while tracking technologies are often marketed as omniscient, students can successfully resist and evade the tools. These technologies elicit strong beliefs among teachers: some feel assured by a cheating-proof, distraction-free learning environment; others are concerned about the extreme nature of the monitoring. But all of the teachers who used the tools experienced a reconfiguring of the school environment to make space for algorithms that changed the nature of deviance, productivity, and accountability. Drawing on literature of surveillance and performativity, we argue that school tracking regimes employing monitoring tools harbor constrictive views of teachers and students’ capacities, as the biases encoded within these tools promote the othering and disciplining of non-normative behaviors related to movement, self-expression, exploration, learning, and creativity. Ultimately, we contend that tracking technologies exceed a necessary level of surveillance in schools while covertly promoting racist and ableist socio-technical arrangements.